Building a Digital Learning Hub: Moodle-Based E-Learning for Sekolah Penggerak in Kolaka Utara - Halil, Nur Ihsan; Nasir, Agus; Syam, Hariadi; Yawan, Hendri (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
Moodle serves as a valuable platform for creating online courses, training, and internet-based education while supporting essential e-Learning content distribution standards, specifically referring to SCORM. This research pursues three primary objectives: (1) the development of Moodle-based e-Learning in SMPN 4 Kolaka Utara, (2) the development of a MOODLE-based e-Learning content package adhering to the SCORM standard, and (3) the comprehensive evaluation of the Moodle-based e-Learning development process. Adopting the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) approach, the outcome of this research is the establishment of an innovative E-learning platform, named mesikolah.com, accessible online via https://mesikolah.com/. These courses meet the stringent SCORM standardization criteria, including Accessibility, Adaptability, Affordability, Durability, Interoperability, and Reusability. Formative evaluation results demonstrate a strong alignment with the chosen research approach, ADDIE, while the summative evaluation reveals positive user feedback, with an impressive 80% satisfaction rate on the e-Learning platform. Although this research focuses on the e-Learning development stage and content package preparation, further investigations are warranted, such as classroom action research. Notably, the current content package predominantly comprises text and flash presentations, necessitating future development of diverse media types, such as video on demand or video streaming.